Методи оцінки якості палива для підвищення надійності дизельних систем живлення - Савченко, Анатолій Вікторович; Кіценко, Петро Борисович (Національний технічний університет "Харківський політехнічний інститут", 2025)
У статті проведено порівняльний аналіз сучасних лабораторних та бортових технологій контролю якості дизельного палива, що мають критичне значення для забезпечення стабільної роботи систем живлення типу Common Rail в умовах експлуатації. Актуальність дослідження зумовлена потребою підвищення надійності та екологічної безпеки дизельних двигунів на фоні зростаючих вимог до паливної економічності та адаптації до концепції Індустрії 5.0. Метою роботи є систематизація знань про існуючі методи оцінювання якості палива та обґрунтування перспектив використання бортових сенсорних систем як елементу превентивного обслуговування дизельних систем. Основними завданнями є: аналіз стандартних лабораторних методик визначення фізико-хімічних характеристик палива (цетанове число, густина, в’язкість, вміст сірки, FAME, води та ароматичних сполук), огляд існуючих технологій для інтеграції засобів діагностики безпосередньо на борту транспортного засобу, а також оцінка точності, надійності й доцільності таких технологій у практичному застосуванні. У роботі використано методи порівняльного аналізу літературних джерел, стандартів та патентної документації, а також методологію технічної експертизи конструкцій і принципів роботи сенсорних систем.

The article presents a comparative analysis of modern laboratory and on-board technologies for monitoring the quality of diesel fuel, which are critically important for ensuring the stable operation of Common Rail fuel supply systems under operating conditions. The relevance of the research is due to the need to increase the reliability and environmental safety of diesel engines against the background of growing requirements for fuel efficiency and adaptation to the Industry 5.0 concept. The purpose of the work is to systematize knowledge about existing methods for assessing fuel quality and to justify the prospects of using on-board sensor systems as an element of preventive maintenance of diesel systems. The main tasks are: analysis of standard laboratory methods for measuring the physicochemical characteristics of fuel (cetane number, density, viscosity, sulfur content, FAME, water, and aromatic compounds), review of existing technologies for integrating diagnostic tools directly on board a vehicle, and evalua-tion of the accuracy, reliability, and practical applicability of such technologies. The study uses methods of comparative analysis of literature sources, standards, and patent documentation, as well as the methodology of technical evaluation of the design and operating principles of sensor systems. The novelty of the approach lies in the comprehensive comparison of the capabilities of traditional laboratory diagnostics with the results provided by modern on-board sensors based on tuning fork technology, near-infrared spectroscopy, ultrasonic, MEMS, and dielectric technologies. The research results show that most laboratory methods provide high accuracy, but are resource-intensive, poorly suited to real-time conditions, and not always informative for rapid response of engine control systems.
Fuel quality assessment methods for improving the reliability of diesel fuel systems
Keywords: дизельне паливо; Common Rail; моніторинг якості палива; бортові сенсори; лабораторний аналіз; цетанове число; діелектрична проникність; NIR-спектроскопія; diesel fuel; Common Rail; fuel quality monitoring; on-board sensors; laboratory analysis; cetane number; dielectric constant; NIR spectroscopy